2018
DOI: 10.1002/gj.3095
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic uplift of the Qimantage Mountains, northeastern Tibet: Contraints from provenance analysis of Cenozoic sediments in Qaidam Basin

Abstract: Qimantage Orogen as the western part of East Kunlun Mountains is located in the northeastern margin of the Tibet Plateau. In this contribution, detrital zircon age spectra combined with heavy mineral analysis of Cenozoic sediments from Qaidam Basin were applied to reveal the uplift history of Qimantage Mountains. Our results show that the Cenozoic staged uplift of the Qimantage Mountains exhibit eastward and northward uplift characteristics. From the middle Eocene to Quaternary, there are three major uplift st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…previous detrital zircon geochronology study (Bush et al, 2016;Cheng et al, 2016a;Cheng et al, 2016b;Wang et al, 2017b). NEQB and SGHB are abbreviations of northeastern are mainly compiled from this study and previous work (Bush et al, 2016;Cheng et al, 2016a;Cheng et al, 2016b;Wang et al, 2017b;Zhou et al, 2018). The locations of those studies are shown in Fig.…”
Section: Increased Precipitation May Have Drive N Basin-scale Transgression Processes In Thementioning
confidence: 92%
See 1 more Smart Citation
“…previous detrital zircon geochronology study (Bush et al, 2016;Cheng et al, 2016a;Cheng et al, 2016b;Wang et al, 2017b). NEQB and SGHB are abbreviations of northeastern are mainly compiled from this study and previous work (Bush et al, 2016;Cheng et al, 2016a;Cheng et al, 2016b;Wang et al, 2017b;Zhou et al, 2018). The locations of those studies are shown in Fig.…”
Section: Increased Precipitation May Have Drive N Basin-scale Transgression Processes In Thementioning
confidence: 92%
“…Meanwhile, the appearance of aeolian deposits in the Lanzhou basin (Zhang et al, 2014) and the Taklimakan desert (Heermance et al, 2018) to the west also support the reginal aridification in the western China since the middle Miocene. (Bush et al, 2016;Cheng et al, 2016a;Cheng et al, 2016b;Wang et al, 2017b;Zhou et al, 2018), which reveals that potential source areas became much more diverse gradually from the Lulehe Fm., to Xiaganchaigou Fm. and to Shangganchaigou Fm.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 97%
“…China (Liu et al, 2011b). Based on both regional evidence and global cooling at this time (Zachos et al, 2001), Cheng et al, 2016b; Wang et al, 2017b;Zhou et al, 2018), which reveals that potential source areas became much more diverse gradually from the Lulehe Fm., to Xiaganchaigou…”
Section: Seismic Datamentioning
confidence: 99%
“…Z. Zhu et al, 1989) (Figure 2). In addition to recent intense tectonic activities, the Kunlun Mountains continue to rise, while the QB is relatively declining (Y. D. Wang et al, 2012; Zhou et al, 2018). A massive earthquake (Ms 8.1) occurred on 14 November 2001, and ruptured a 450‐km long stretch of the sinistral Kunlun strike‐slip fault in the eastern Kunlun fault zone (Klinger et al, 2005; Yin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al, 1989) (Figure 2). In addition to recent intense tectonic activities, the Kunlun Mountains continue to rise, while the QB is relatively declining (Y. D. Wang et al, 2012;Zhou et al, 2018).…”
Section: Mechanism Governing the Rapid Groundwater Circulation Systemmentioning
confidence: 99%